Quantitation of Compounds in Wine Using 1H NMR Spectroscopy: Description of the Method and Collaborative Study. (4th December 2019) - Godelmann, Rolf; Kost, Christian; Patz, Claus-Dieter; Ristow, Reinhard; Wachter, Helmut
Abstract: To examine whether NMR analysis is a suitable method for the quantitative determination of wine components, an international collaborative trial was organized to evaluate the method according to the international regulations and guidelines of the German Institute for Standardization/International Organization for Standardization, AOAC INTERNATIONAL, the International Union of Pure and Applied Chemistry, and the International Organization of Vine and Wine. Sugars such as glucose; acids such as malic, acetic, fumaric, and shikimic acids (the latter two as minor components); and sorbic acid, a preservative, were selected for the exemplary quantitative determination of substances in wine. Selection criteria for the examination of sample material included different NMR spectral signal types (singlet and multiplet), as well as the suitability of the proposed substances for manual integration at different levels of challenge (e.g., interference as a result of the necessary suppression of a water signal or the coverage of different typical wine concentration ranges for a selection of major components, minor components, and additives). To show that this method can be universally applied, NMR measurement and the method of evaluation were not strictly elucidated. Fifteen international laboratories participated in the collaborative trial and determined six parameters in 10 samples. The values, in particular the reproducibility SD (SR ), were compared with the expected Horwitz SD (SH ) by forming the quotient SR /SH (i.e., the HorRat value). The resulting HorRat values of most parameters were predominantly between 0.6 and 1.5, and thus of an acceptable range.